Efeito da aplicação foliar de ácidos graxos na "Via das Lipoxigenases" de plantas de soja - Batista Rosa Bárbara (Química Nova, 2002)
The involvement of lipoxygenase isozymes in several physiological processes of plants has been described but their role is not well understood and more biochemical studies are needed to elucidate the role of the "Lipoxygenase Pathway" in plant physiology. Thus, the biochemical and kinetic characterization of a lipoxygenases "pool" from soybean leaves was carried out. Two genotypes were used: IAC-100 (a normal variety having lipoxygenases in the seeds) and IAC-100 TN (genetically modified genotype, which is devoid of lipoxygenases in the seeds). The plants were submitted to the application of fatty acids (lipoxygenase substrates) on leaves. The results of the biochemical and kinetic studies of lipoxygenase isozymes from leaves of the two genotypes analysed showed that genetic removal of lipoxygenase from seeds did not affect the response of the plant to the treatment, since both genotypes showed similar results.